From Customary Sanctions to State Law: Legal Intervention in Social Exclusion and Informal Punishment in Indonesian Villages - Rena Yulia; Ridwan Arifin (The Indonesian Journal of Legal Intervention in Social Problems, 2026)
Customary and community-based sanctions continue to play an important role in regulating social behavior in Indonesian villages. Public reprimands, exclusion from community activities, informal fines, social boycotts, and other forms of customary punishment may contribute to social order, yet they can also produce disproportionate consequences and undermine individual rights. This article examines the boundaries between legitimate community-based social control and unlawful forms of social exclusion, focusing on the role of state law as an instrument of legal intervention. Adopting a socio-legal approach, the study analyzes the interaction between customary norms, village governance, social expectations, and national legal standards concerning equality, dignity, and access to justice. The article argues that the state's response should neither automatically suppress customary mechanisms nor uncritically legitimize them. Instead, legal intervention should establish substantive boundaries that distinguish socially legitimate dispute resolution from coercive, discriminatory, or degrading punishment. The contribution of this study lies in developing a framework for legally responsive pluralism in village governance, whereby customary practices may coexist with state law while remaining subject to fundamental rights and procedural safeguards.